2016
DOI: 10.1148/radiol.2016142796
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hip Failure Load: In Vitro Study of 80 Femurs Using Three Imaging Methods and Finite Element Models—The European Fracture Study (EFFECT)

Abstract: Purpose To evaluate the performance of three imaging methods (radiography, dual-energy x-ray absorptiometry [DXA], and quantitative computed tomography [CT]) and that of a numerical analysis with finite element modeling (FEM) in the prediction of failure load of the proximal femur and to identify the best densitometric or geometric predictors of hip failure load. Materials and Methods Institutional review board approval was obtained. A total of 40 pairs of excised cadaver femurs (mean patient age at time of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…The sensitivity of fracture force to force direction is a reflection of proximal femur anatomy, with cadaveric studies demonstrating that the proximal femur can withstand forces two-to-four times greater in the single-limb stance direction than forces in a posterolateral fall direction [39, 40]. During a sideways fall onto the greater trochanter, the stress pattern within the femoral neck is reversed from that experienced during weight-bearing.…”
Section: Fracture Prone Regions Within the Proximal Femurmentioning
confidence: 99%
“…The sensitivity of fracture force to force direction is a reflection of proximal femur anatomy, with cadaveric studies demonstrating that the proximal femur can withstand forces two-to-four times greater in the single-limb stance direction than forces in a posterolateral fall direction [39, 40]. During a sideways fall onto the greater trochanter, the stress pattern within the femoral neck is reversed from that experienced during weight-bearing.…”
Section: Fracture Prone Regions Within the Proximal Femurmentioning
confidence: 99%
“…Of note, textural analysis of the femur on pelvic radiographs is another option for assessment of fracture risk and is better for prediction of fragility fracture compared with DXA (56). In a recent cadaver study (57), investigators compared finite element–based quantitative CT (as used in our model) with DXA, radiography, and CT-based bone measurement for femur fracture prediction. That study showed that quantitative CT was the best method for prediction of failure load (57).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cadaver study (57), investigators compared finite element–based quantitative CT (as used in our model) with DXA, radiography, and CT-based bone measurement for femur fracture prediction. That study showed that quantitative CT was the best method for prediction of failure load (57). …”
Section: Discussionmentioning
confidence: 99%
“…4,[11][12][13][14] In addition to DXA and QCT, more researchers tend to use the finite element analysis (FEA) method to investigate bone features, 4,[15][16][17][18] since FEA reveals information of the three-dimensional (3D) morphology, the material property and the loading distribution of bone, which may provide a more accurate bone strength prediction. 4,16,17,[19][20][21][22][23] Among all factors that affect FEA analysis results, a critical one is bone geometric model. 22 Digital Imaging and Communications in Medicine (DICOM) is the international standard of medical imaging.…”
Section: Introductionmentioning
confidence: 99%